Strategies in e-business : positioning and social networking in online markets - Palacios-Marques, Daniel; Peris-Ortiz, Marta Peris; Vendrell, Eduardo; Ferri-Ramirez, Cesar; Gil-Pechuan, Ignacio (Springer US, 2014)
In this volume, the authors apply insights from a variety of perspectives to explore the alignment among strategy, organization design, process and human resource management, and e-business practices on developing successful social networking programs-with particular regard to applying such initiatives against the backdrop of the global financial crisis and challenges to traditional business models. Showcasing in-depth case studies, the authors present emerging approaches to analyze the impact of investment in social networking sites, aligning internal resources, and measuring effects on positioning, branding, and new business creation.   The fact that a growing proportion of the world population has a relationship with social networking sites could prove very valuable for companies. The question is whether this represents a business opportunity, whether companies know how to make the most of it and if they will make the necessary efforts to adapt to these new platforms. In the modern world, social networking sites have enormous potential for large as well as small and medium-sized enterprises (SMEs); most companies are aware of the need for a presence on social networking sites, but at present their e-business strategies are part of their medium and long-term strategic planning and only a small percentage have been put into practice.   In short, this book attempts to answer the following questions: Is there a business opportunity for companies on social networking sites? Do they know how to make the most of it? Are they willing to make the necessary effort to adapt? Can e-business strategies contribute to company creation and the success of already existing businesses? And if so, how?